Venezuela: The Political Crisis of Post-Chavismo - López Maya, Margarita (Social justice, 2013)
The article presents an analysis of political developments and crisis in Venezuela. Topics discussed include political imbalances in the Venezuelan society during the illness of Venezuelan President Hugo Chávez which is seen as dismantling of the liberal democratic institutions, continuous growth of social violence such as murders, robberies, and kidnappings, and acceleration in Rentier socialism during the first presidency of Carlos Andres Perez in the 1970s.